Pengaruh Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai : (Kajian Studi Literatur Manajemen Kinerja) - Dinda Adelia; Nur Putri Cahyaningsih; Nabella Nur Afiyah; Indah Rizki Maulia (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This article provides a detailed literature review on the effects of workload and work environment on employee performance. This article examines the theoretical concepts, empirical findings and identified relationships between employee workload and work environment conditions and individual performance outcomes using a literature synthesis. We hope this overview provides an overall overview of the key factors that influence employee efficiency and productivity in different organizational contexts. Based on the literature review, there is strong evidence that a workload appropriate to an individual's abilities can improve employee motivation and performance. Conversely, excessive workload can lead to fatigue and reduced productivity. Additionally, a supportive, encouraging, and well-resourced work environment can improve employee performance. We also found that factors such as social support and opportunities for self-development in the work environment may play an important role in moderating the relationship between workload, work environment, and employee performance.